O impacto do background familiar sobre o esforço e sua influência no resultado econômico dos indivíduos: uma aplicação do Modelo de Roy para o Brasil - Souza, Wallace Patrick Santos de Farias (2014)
This study measures the influence that parents' education has on the effort and the level of income earned by individuals. The effort will be approximated by education levels, dividing the individuals into two groups, ie, no upper level ("Low"), representing individuals who play a lesser effort, and higher level ("High") indicating a higher effort. The empirical estimation strategy was based on three steps: i) estimating the average effect of conventional treatment by different methods, following Heckman and Honore (1990) and Heckman and Vytlacil (1999), ii) the bounds of variation of Shaikh and Vytlacil (2004) for the impact of treatment and iii) a test of robustness for estimating instrumental variable that includes the unemployment rate as a way to endogenize the years of schooling of individuals. The results, based on data from the National Sample Survey (PNAD) of 1996, indicate a significant effect of education of father and mother, especially in less educated individuals.This can be explained, among other factors, by the lower level of income and consequently a higher degree of dependence on these individuals of their family background, following the assumptions of unequal opportunities. Finally, the non-use of instrumental variable coefficients tends to overestimate the effect of treatment, especially education of the father rather than the mother's education.